Can law save the forest?: lessons from Finland and Brazil - Hirakuri, S.R. (Center for International Forestry Research, 2003)
Forests are among the most diverse and widespread ecosystems on earth; they provide mankind with a wide range of economic, social and environmental benefits. However, the forests are increasingly being threatened by unsustainable logging practices. Rampant deforestation in the tropics and international pressures have led government of tropical forest countries to take actions to promote forest management of natural forests. However, in most countries forest management has been implemented improperly. Thus, low compliance with existing forest management laws rather than lack of law, is often a leading cause of unsustainable forestry practices in many tropical forest countries. This study examines the contrast of Brazil, a low compliance country, with Finland, the most successful country. Focus is given to the Finnish model of forestry law enforcement, concentrating on factors that can be adapted to Brazil and other tropical forest countries. Some specific recommendations have been drawn from this cross-case study. These lessons might be useful for Brazil and other tropical forest countries which are trying to improve their forestry law enforcement system.